The forgotten girls - Potts, Monica (New York : Random House, 2023)
"Growing up gifted and poor in small-town Arkansas, Monica and Darci became fast friends. The girls bonded over a shared love of reading and learning, even as they navigated the challenges of their declining town and tumultuous family lives-broken marriages, alcohol abuse, and shuttered stores and factories. They pored over the giant map in their middle school classroom, tracing their fingers over the world that awaited them, vowing to escape. In the end, Monica got out, but Darci, along with the rest of their circle of friends, did not. Years later, working as a journalist covering poverty, Monica discovered what she already intuitively knew about the women in Arkansas: Their life expectancy had steeply declined-the sharpest such fall in a century. Most painfully, her once talented and ambitious best friend was now a single mother of two, addicted to meth and prescription drugs, jobless and nearly homeless. What had happened in the years since Monica had left? Why had she escaped while Darci hurtled toward what Monica fears will be a tragic end? What was killing poor white women-and would Darci survive her own life"--
Place -- Religion -- The School Hill house -- Boy crazy -- The rebellion -- The summer in New York -- The escape plan -- Trauma -- The goodbye -- Leaving and staying -- The party house -- Motherhood -- The money -- The Trouble -- The trailer -- Moving -- The downward spiral.
Keywords: Potts, Monica; Potts, Monica -- Friends and associates; Women journalists -- United States -- Biography; Female friendship -- Arkansas -- Clinton; Poor women -- Arkansas -- Clinton -- Social conditions; Rural poor -- Arkansas -- Clinton -- Social conditions; Women drug addicts -- Arkansas -- Clinton; Arkansas -- Biography; Biographies; Print books